Teologi Kurikulum: Kristologi, Fondasi, Struktur, dan Dinamika Transformasional Pendidikan Kristen (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
This study examines the role of Christology as a foundational theological framework in the development of a Christian education curriculum aimed at the holistic transformation of learners. The research focuses on the dynamics of curriculum design, its structural underpinnings, and the selection of content that harmoniously integrates faith, knowledge, and socio-cultural context. Employing a systematic literature review methodology, the study critically analyses relevant theories and practices within curriculum theology. The findings reveal that Christology functions as the central axis for integrating faith and learning, thereby fostering a curriculum that is both adaptive and meaningful. These results underscore the imperative of maintaining a balance between theological values and academic advancement within Christian education. The originality of this research lies in its comprehensive synthesis of Christological perspectives with the transformational dimensions of curriculum development, an area seldom explored in depth within Christian educational discourse.